Pengaruh Likuiditas, Profitabilitas dan Rentabilitas Terhadap Harga Saham Pada Perusahaan Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia - Glistin Azuma Siregar; Husni Mubarak (Jurnal Riset Akuntansi dan Bisnis, 2023)
The purpose of this study was to determine the effect of Current Ratio, Return On Assets and Return On Equity simultaneously on Stock Prices in Food and Beverage Companies Listed on the Indonesia Stock Exchange. This study uses data from the financial statements of food and beverage companies listed on the Indonesia Stock Exchange for 2016 – 2020. Data analysis uses Multiple Linear Regression Tests, hypothesis testing uses the coefficient of determination test (R2), partial test (t-test) and simultaneous test ( F-test) while data processing uses SPSS 22.0. The results of this study indicate that the Current Ratio, Return On Assets and Return On Equity simultaneously influence the stock prices of Food and Beverage Companies listed on the Indonesia Stock Exchange in 2016-2020, while the partial test results show that the current ratio has a negative and insignificant effect on stock prices while return on assets and return on equity have no effect and are not significant on stock prices at Food and Beverage Companies listed on the Indonesia Stock Exchange in 2016-2020